False consciousness in Manhattan as depicted in Cosmopolis - Husaini, Irzam; Ruslianti, Atikah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
Cosmopolis takes themes around economy, capitalism, Marxism and social class. This study aims to analyse the author’s way to depict false consciousness in Cosmopolis’ “fictionalised” Manhattan through the proletariat’s actions toward the bourgeois main character in keeping on promoting of the latter’s economic interests. The study uses descriptive analytical of qualitative method with Marxist class theory to analyse false consciousness in Manhattan as depicted by the selected proletarian characters who work for the bourgeois main character. The result shows that the proletariat in the book do what they and the society consider to be true by serving the capital owner in return of money which they can use to get better lives, when they should join efforts to tear down the system that keeps them stay in their unfavourable positions as workers.